Do European Parliament elections impact national party system fragmentation? - Dinas, E; Riera, P (SAGE Publications, 2017)
Why have European large parties lost electoral ground in recent decades? Whereas most explanations draw on theories of dealignment, this paper advances a novel, institutional, argument by focusing on the introduction of direct elections to the European Parliament (EP) in 1979. Archetypes of second-order elections, EP elections are characterized by lower vote shares for 1) large and 2) incumbent parties. Bridging the second-order elections theory with theories of political socialization, we posit that voting patterns in EP elections spill over onto national elections, especially among voters not yet socialized into patterns of habitual voting. In so doing, they increase the national vote shares of small parties. This proposition is examined using an instrumental variables approach. We also derive a set of testable propositions to shed light on the underlying mechanisms of this pattern. Our findings show that EP elections decrease support for big parties at the national arena by inculcating voting habits.